Responsibility of Digital-Based Complain Services at the Honor Board of Election Organizers of the Republic of Indonesia (DKPP RI) During Pandemic - Muh. Hasbi Azis Agani; Nuryanti Mustari; Ahmad Harakan; Nursaleh Hartaman (Jurnal Studi Pemerintahan, 2022)
In public services, responsiveness or responsiveness is one of the benchmarks for good governance. Enforcement of the code of ethics against violations of election administration (KPU and Bawaslu) committed by the DKPP RI as an institution for enforcing the code of ethics for election organizers. Data from the DKPP stated that from 2018 to 2021 there were 1,546 complaints that came in through digital media, peaking in 2020 during the pandemic so that in the service of complaints carried out by the DKPP RI RI, it is necessary to have service responsiveness in receiving reports/complaints from reporters, which makes DKPP RI an institution that integrity. This research uses descriptive qualitative method with data analysis using NVivo 12 Plus. By using 6 indicators of responsiveness of the results obtained. The successful achievement of digital-based complaint services at the Dewan Kehormatan Penyelenggara Pemilu Republik Indonesia (DKPP RI) during the pandemic uses 6 indicators, namely “the ability to respond to the community, officers have provided good attitudes and communication; speed of service, officers have shown alertness and sincerity in serving; accuracy of service, officers have been focused and serious in their work; service accuracy, officers have worked in accordance with the SOP; timeliness of service, officers work in accordance with incoming reports; the ability to respond to complaints, officers are able to respond to complaints and provide the best solutions.